Determinants of Corporate Social Responsibility Disclosure: The Moderating Role of Good Corporate Governance - Nida Aufa Al 'Asya; Yuni Utami; Amirah Amirah (Faculty of Economics and Business Universitas Jenderal Soedirman, 2026)
This study aims to analyze the impact of leverage, ability to earn profits, and ecological performance on corporate social responsibility disclosure (CSRD) with good corporate governance (GCG) as moderation variable. Research subjects include entities in the basic materials, energy, industrials, and consumers non cyclicals sectors listed on the lndonesia stock exchange or IDX for 2021–2025 periods. Research sample was determined using using the purposive sampling method and obtaining 24 entities with total of 120 panel data observation data. Analysis data was carried out using a random effect model or REM approach with robust standard error cluster estimation to overcome autocorrelation problems. Research outputs show that leverage then profitability have no significant influence on CSRD, while ecological performance has a positive and significant influence on the level of corporate social responsibility disclosure. Testing the impact of moderation suggests that GCGs proxied using institutional ownership can moderate the linkage of leverage to CSRD in a negative direction, thereby weakening the relationship. On the other hand, GCG has not been proven to moderate the relationship between profitability and environmental performance to CSRD. This finding suggests that ecological performance is a crucial element in driving increased transparency from disclosing corporate social responsibility while the effectiveness of GCG as mechanism is more visible in condition of companies facing leverage pressure.